2002
DOI: 10.1161/01.atv.0000039168.95670.b9
|View full text |Cite|
|
Sign up to set email alerts
|

Improvement of Collateral Perfusion and Regional Function by Implantation of Peripheral Blood Mononuclear Cells Into Ischemic Hibernating Myocardium

Abstract: Objective-This study was performed to evaluate the angiogenic effect of implantation of peripheral blood mononuclear cells (PB-MNCs) compared with bone marrow mononuclear cells (BM-MNCs) into ischemic hibernating myocardium. Methods and Results-A NOGA electromechanical system was used to map the hibernating region and to inject cells.PB-MNCs and BM-MNCs contained similar levels of vascular endothelial growth factor and basic fibroblast growth factor, whereas contents of angiogenic cytokines (interleukin-1␤ and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
70
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(78 citation statements)
references
References 24 publications
8
70
0
Order By: Relevance
“…PB-MNCs effectively improve collateral perfusion primarily through their ability to supply angiogenic factors and cytokines. The implanted PB-MNCs were not incorporated into neocapillaries, whereas the implanted BM-MNCs were shown to differentiate into vascular ECs [18,19]. In addition, it has been shown that re-endothelialization at sites of vascular damage is also modulated by the mobilization and incorporation of BM-derived EPCs [20].…”
Section: Discussionmentioning
confidence: 99%
“…PB-MNCs effectively improve collateral perfusion primarily through their ability to supply angiogenic factors and cytokines. The implanted PB-MNCs were not incorporated into neocapillaries, whereas the implanted BM-MNCs were shown to differentiate into vascular ECs [18,19]. In addition, it has been shown that re-endothelialization at sites of vascular damage is also modulated by the mobilization and incorporation of BM-derived EPCs [20].…”
Section: Discussionmentioning
confidence: 99%
“…86 Others showed that transendocardial delivery of unfractionated autologous BM-MNCs induced collateral formation and rescued ventricular function in hibernating porcine myocardium. [87][88][89][90] Orlic et al reported that implantation of bone marrow-derived Lin Ϫ /c-kit ϩ cells, a subpopulation of BM-MNCs, into the infarct border enhanced new vessel formation. 91 In rats with limb ischemia, local intramuscular delivery of autologous BM-MNCs restored blood flow and exercise in association with enhanced neovascularization of the ischemic muscle.…”
Section: Cell Therapy For Myocardial and Peripheral Ischemic Disease mentioning
confidence: 99%
“…This hypothesis was strengthened by Kamihata et al's group showing an increased number of arterioles in response to peripheral blood mononuclear cells (PBMCs) and BMMC injection in the ischaemic myocardium of a pig model of AMI. 9 After the first clinical trials of intracoronary infusion of BMMCs after AMI in patients showed the method to be safe and feasible, 10,11 large-scale randomised trials were initiated to further evaluate the therapeutic effects of BMMC therapy. In the largest study so far, the REPAIR-AMI trial, 204 patients with AMI were randomly assigned to treatment with intracoronary infusion of BMMCs or placebo.…”
Section: Introductionmentioning
confidence: 99%
“…17 Based on the study by Kamihata et al, the beneficial effects of the BMMCs can be attributed to the paracrine effects of all mononuclear cell subsets, rather than the progenitor subpopulation. 18 For that reason, a patient group receiving intracoronary autologous PBMCs was included in the trial. A total of 200 patients with AMI treated with primary PCI with stent placement underwent magnetic resonance imaging (MRI) followed by intracoronary infusion of autologous BMMCs, intracoronary infusion of autologous PBMCs, or standard therapy (randomly assigned to a 1:1:1 ratio).…”
Section: Introductionmentioning
confidence: 99%